Acylation of Anthocyanins and Their Applications in the Food Industry: Mechanisms and Recent Research Advances - Xiu’er Luo; Ruoyong Wang; Jinhua Wang; Ying Li; Huainan Luo; Shi Chen; Xin’an Zeng; Zhong Han (Foods, 2022)
Anthocyanins are extensively used as natural non-toxic compounds in the food industry due to their unique biological properties. However, the instability of anthocyanins greatly affects their industrial application. Studies related to acylated anthocyanins with higher stability and increased solubility in organic solvents have shown that the acylation of anthocyanins can improve the stability and fat solubility of anthocyanins. However, relevant developments in research regarding the mechanisms of acylation and applications of acylated anthocyanins are scarcely reviewed. This review aims to provide an overview of the mechanisms of acylation and the applications of acylated anthocyanins in the food industry. In the review, acylation methods, including biosynthesis, semi-biosynthesis, and chemical and enzymatic acylation, are elaborated, physicochemical properties and biological activities of acylated anthocyanins are highlighted, and their application as colourants, functionalizing agents, intelligent indicators, and novel packaging materials in the food industry are summarized. The limitations encountered in the preparation of acylated anthocyanins and future prospects, their applications are also presented. Acylated anthocyanins present potential alternatives to anthocyanins in the food industry due to their functions and advantages as compared with non-acylated analogues. It is hoped that this review will offer further information on the effective synthesis and encourage commercialization of acylated anthocyanins in the food industry.